Revıew Of The Hıstory And Restoratıon Of Mor Efrem Monastery In Mardın - Turkıye - SEDES , Fatma (Architecture Image Studies, 2023)
Architectural structures that are the product of different cultures in Mardin, present very rich images in terms of architectural form, construction technique and ornamentation. These values, shaped by geography as well as cultural richness and diversity, are the works that shape the city identity unique to Mardin. One of them is Mor Efrem Monastery, which is one of the most important of the Mardin monasteries. As Mor Efrem Monastery is a cultural and religious work, it is important to consider it as a humanitarian duty to keep it alive and move it to the next times. With this study, it is aimed to transfer the structure to the next times. In the archive records scan of Mor Efrem Monastery, no information or document was found that the restoration project was drawn. Within the scope of this study, the architectural features were examined and the deteriorations in the building were specified, the stages of the restoration work in which traditional construction techniques and consolidation methods were applied will be explained. The building will be strengthened structurally, and the structural elements with wear and deterioration will be repaired by adhering to the original condition. The basis of interventions in restoration ; Cleaning, rehabilitating and reintegration works.